Study on hydrogeochemical assessment, groundwater quality index for drinking, seawater mixing index and human health risk assessment of nitrate and fluoride - Ravindiran G.; Janardhan G.; Rajamanickam S.; Sivarethinamohan S.; Murali V.; Hayder G. (Elsevier B.V., 2025)
The present study examined the impact of groundwater quality on drinking and irrigation purposes in the coastal district Ramanthapuram of Tamil Nadu State of Indian country. A total of 26 sampling stations were studied to examine the groundwater water quality index (WQI) using the water quality analysis. Out of 26 stations, it was observed that 19 stations' groundwater was unfit (WQI>100), 5 stations was very poor (WQI: 76-100), and 2 stations were poorly (WQI:51-75) affected and not suitable for drinking purposes. The Seawater Mixing Index (SMI) was also studied to understand the seawater intrusion into the groundwater and 61% of the sampling stations' SMI values were above 1 confirming the seawater intrusion into groundwater. The study also examined the hydrogeochemical process, to understand the water chemistry by developing a Piper trilinear graph and Gibbs plot. Further to understand the groundwater quality more statistically, a statistical analysis was conducted. Human Health Risk Assessment (HHRA) was also computed to understand the risk factors for children and Adults. For Nitrate, 75% (children) and 57% (adults) of the sampling station have HI values > 1 and for Fluoride, 34% (children) of the sampling station have HI values > 1. To assess the suitability of the groundwater for irrigation purposes, salinity hazard, sodium adsorption ratio, magnesium adsorption ratio, and Kelly's index were calculated. ? 2024 Elsevier B.V.